EFEKTIVITAS MODEL PEMBELAJARAN MULTILITERASI TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR - Yuliati, Yuyu; Febriyanto, Budi (Journal of Innovation in Primary Education, 2022)
This research is motivated by the low ability of scientific literacy of elementary school students while scientific literacy itself is one of the abilities that must be mastered by students to be able to face various life problems. Scientific literacy skills should be trained and developed in learning by implementing various innovative learning strategies with the hope of helping students master these abilities. The purpose of this study was to determine the effectiveness of the multiliteracy learning model on the scientific literacy abilities of elementary school students. This study used a quasi-experimental method with a pretest-posttest control group design. The results of the study show that the multiliteracy learning model is effective in increasing the scientific literacy of elementary school students.